2001
DOI: 10.1088/0953-4075/34/3/308
|View full text |Cite
|
Sign up to set email alerts
|

An efficient, selective collisional ejection mechanism for inner-shell population inversion in laser-driven plasmas

Abstract: A theoretical analysis of laser-driven collisional ejection of inner-shell electrons is presented to explain the previously observed anomalous kilovolt L-shell x-ray emission spectra fkom atomic Xe cluster targets excited by intense sub-picosecond 248nrn ultraviolet radiation [A. McPherson et al., Nature 370, pp. 631-634 (1994)].For incident ponderomotively-driven electrons photoionized by strong above threshold ionizatio~the collisional ejection mechanism is shown to be highly l-state and signifka.ntly n-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 61 publications
4
27
1
1
Order By: Relevance
“…Our results contradict previous results [4,7,8] both on line assignments and wavelength dependency. An extensive theoretical work is needed before interpretation of the observed spectral shapes, intensity threshold and possible selection rule on vacancy production can be made.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results contradict previous results [4,7,8] both on line assignments and wavelength dependency. An extensive theoretical work is needed before interpretation of the observed spectral shapes, intensity threshold and possible selection rule on vacancy production can be made.…”
Section: Resultscontrasting
confidence: 99%
“…Kondo et al [4] have assign the two group of lines to 3d →2p transitions in multicharged (25 ≤ q ≤ 35) Xe ions with one or two 2p vacancies. The production of such multiple inner-shell vacancies has been interpreted [7,8] as due to a "coherent, ordered many-electron motion" acting as a single heavy, highly charged, particle. From our calculations, we find however that the energy difference between transitions involving one or two 2p vacancies amounts to ~ 120 eV (0.08 Å) on the average, a value much too small to account for the observed energy difference between the two groups of transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms for the increased ionization (as compared to single atoms in the same laser field) have been proposed. Boyer et al [9] suggested that collective electron motion (CEM) inside the cluster is responsible for inner shell vacancies the corresponding radiation of which was observed in experiments [10]. Rose-Petruck et al [11] introduced the socalled "ionization ignition" (IONIG) where the combined field of the laser and the ions inside the cluster leads to increased inner ionization, i.e., electrons are more easily removed from their parent ion as if there was the laser field alone.…”
Section: Introductionmentioning
confidence: 97%
“…Krainov and Smirnov investigated a broad range of issues involving the laser cluster interaction and coupling problem extending from cluster formation to X-ray generation [12]. Schroeder et al introduced the so-called "collective oscillation model" for small clusters (10e30 Å) [13,14]. In its coherent motion the outer electrons behave like a giant quasi-particle, hitting the cluster with energy of tens of keV causing inner-shell ionization.…”
Section: Introductionmentioning
confidence: 99%